Polyoxometalates as a Novel Class of Artificial Proteases: Selective Hydrolysis of Lysozyme under Physiological pH and Temperature Promoted by a Cerium(IV) Keggin‐Type Polyoxometalate. Issue 8 (9th January 2013) - Stroobants, Karen; Moelants, Eva; Ly, Hong Giang T.; Proost, Paul; Bartik, Kristin; Parac‐Vogt, Tatjana N.
Abstract Hen‐egg‐white lysozyme (HEWL) is specifically cleaved at the Trp28–Val29 and Asn44–Arg45 peptide bonds in the presence of a Keggin‐type [Ce(α‐PW11O39)2]10− polyoxometalate (POM; 1) at pH 7.4 and 37 °C. The reactivity of 1 towards a range of dipeptides was also examined and the calculated reaction rates were comparable to those observed for the hydrolysis of HEWL. Experiments with α‐lactalbumin (α‐LA), a protein that is structurally highly homologous to HEWL but has a different surface potential, showed no evidence of hydrolysis, which indicates the importance of electrostatic interactions between 1 and the protein surface for the hydrolytic reaction to occur. A combination of spectroscopic techniques was used to reveal the molecular interactions between HEWL and 1 that lead to hydrolysis. NMR spectroscopy titration experiments showed that on protein addition the intensity of the 31P NMR signal of 1 gradually decreased due to the formation of a large protein/polyoxometalate complex and completely disappeared when the HEWL/1 ratio reached 1:2. Circular dichroism (CD) measurements of HEWL indicate that addition of 1 results in a clear decrease in the signal at λ=208 nm, which is attributed to changes in the α‐helical content of the protein. 15N–1H heteronuclear single quantum coherence (HSQC) NMR measurements of HEWL in the presence of 1 reveal that the interaction is mainly observed for residues that are located in close proximity to the first site in the α‐helical part of the structure (Trp28–Val29). The less pronounced NMR spectroscopic shifts around the second cleavage site (Asn44–Arg45), which is found in the β‐strand region of the protein, might be caused by weaker metal‐directed binding, compared with strong POM‐directed binding at the first site.